Regulation of protein prenylation - Jung, Dominik; Bachmann, Hagen S. (Biomedicine & pharmacotherapy, 2023)
Prenyltransferases (PTases) are known to play a role in embryonic development, normal tissue homeostasis and cancer by posttranslationally modifying proteins involved in these processes. They are being discussed as potential drug targets in an increasing number of diseases, ranging from Alzheimer's disease to malaria. Protein prenylation and the development of specific PTase inhibitors (PTIs) have been subject to intense research in recent decades. Recently, the FDA approved lonafarnib, a specific farnesyltransferase inhibitor that acts directly on protein prenylation; and bempedoic acid, an ATP citrate lyase inhibitor that might alter intracellular isoprenoid composition, the relative concentrations of which can exert a decisive influence on protein prenylation. Both drugs represent the first approved agent in their respective substance class. Furthermore, an overwhelming number of processes and proteins that regulate protein prenylation have been identified over the years, many of which have been proposed as molecular targets for pharmacotherapy in their own right. However, certain aspects of protein prenylation, such as the regulation of PTase gene expression or the modulation of PTase activity by phosphorylation, have attracted less attention, despite their reported influence on tumor cell proliferation. Here, we want to summarize the advances regarding our understanding of the regulation of protein prenylation and the potential implications for drug development. Additionally, we want to suggest new lines of investigation that encompass the search for regulatory elements for PTases, especially at the genetic and epigenetic levels. •Protein prenylation is relevant in diseases ranging from cancer to diabetes.•Complex regulatory networks impede transition of interfering drugs into clinic.•In vitro data call for in vivo evaluation of prenylation regulation by drugs and diet.•More research regarding (epi-)genetic regulation of prenylation is required.•Deeper understanding of prenylation promises drugs for novel therapeutic approaches.